Characteristics of drug usage statistics in hypertensive patients with diabetes at Saint paul general Hospital - Bui, Thi Hao; Tran, Thi Thu Huong; Nguyen, Thi Hong Lam; Ho, Nhat Vinh; Le, Thanh Liem (Tạp chí Y Dược cổ truyền Việt Nam, 2024)
Objective: To analyze the characteristics of drug usage statistics in hypertensive patients with diabetes at the outpatient Department of Saint Paul General Hospital. Subjects and methods: A retrospective study based on information collected from the medical records of patients diagnosed with hypertension and diabetes who received outpatient treatment at Saint Paul General Hospital from September 2022 to December 2022. Results: The average age of the study group was 70.28 ± 7.2 years. The gender ratio was nearly equal, with 49% male and 51% female. The most commonly used drug groups were ARBs, followed by CCBs. Most patients used a single diabetes medication, with biguanides (Metformin) being the most commonly used, followed by Sulfonylureas. Insulin was used in nearly one-third of diabetes treatment prescriptions such as: 23.8% of patients (T0); 24.8% of patients (T1); 28.6% of patients (T2). There was 83% of patients in the study sample had lipid disorders. At T0, 63.81% of patients used statins, and 15.24% used Fenofibrate. Conclusion: The study results show that 105 patients were annalyzed regarding demographic, drug usage characteristics. The majority of outpatient patients were hypertention with diabetes, suffering from comorbid lipid metabolism disorders.